Revision of the Palaearctic and Oriental species of the genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae) - Lee, Chi-Feng; Beenen, Ron (Zootaxa, 2017)
Forty species of the genus Oides Weber, 1801 are considered as valid in the Palaearctic and Oriental regions. Six new species are described: O. bezdeki sp. nov., O. hsui sp. nov., O. takizawai sp. nov., and O. wangi sp. nov. from Sulawesi (Indonesia); O. boreri sp. nov. from Laos; and O. geiseri sp. nov. from India, Nepal, and Myanmar. The following synonymies are proposed: O. maculicollis Jacoby, 1886 as a junior synonym of O. apicalis Jacoby, 1883; O. niasensis Bowditch, 1925 as a junior synonym of O. duodecimpunctata (Clark, 1865); A. sumatrensis Blanchard, 1853, A. philippinensis Boheman, 1859, O. flavipes Duvivier, 1884, O. abdominalis Duvivier, 1884, O. subtilissima Duvivier, 1884, O. flavida Duvivier, 1884, O. elliptica Duvivier, 1884, O. marcida Duvivier, 1884, O. rhabodscelis Weise, 1922, O. bakeri Laboissière, 1925, and O. ovalis Laboissière, 1925 as junior synonyms of O. flava (Olivier, 1807); O. bengalensis Maulik, 1936 as a junior synonym of O. innocua Gahan, 1891; O. violaceipennis Duvivier, 1884 as a junior synonym of O. metallica Jacoby, 1884; O. indosinensis Laboissière, 1927 as a junior synonym of O. palleata (Fabricius, 1801); O. sternalis Weise, 1913 as a junior synonym of O. quadriguttata Duvivier, 1884; O. gyironga Chen & Jaing, 1981 as a junior synonym of O. scutellata (Hope, 1830); O. indica Baly, 1879 and O. chinensis Weise, 1922 as junior synonyms of O. tarsata (Baly, 1865); O. tibialis Duvivier, 1884 as a junior synonym of O. vixilla Duvivier, 1884. Oides epipleuralis Laboissière is removed from synonymy with O. laticlava (Fairmaire, 1889); O. laticlava (Fairmaire, 1889) removed from synonymy with O. maculata (Olivier, 1807); O. thibettana Jacoby, 1900 and O. tibiella Wilcox, 1971 removed from synonymies with O. tarsata (Baly, 1865). Neotypes are designated for Adorium maculatum Olivier, 1807; A. subhemisphaericum Guérin-Méneville, 1830; A. diardi Guérin-Méneville, 1830; O. chinensis Weise, 1922; and O. leucomelaena Weise, 1922. Host plant information is provided when known.